DNA-enabled rational design of fluorescence-Raman bimodal nanoprobes for cancer imaging and therapy - Suchetan Pal (Nature Portfolio, 2019)
Currently available Raman scanners are limited in speed to acquire images of clinically relevant sizes in cancer imaging. Here, the authors developed a DNA based design principle for Raman-Fluorescence bimodal nanoparticles and demonstrate real-time, high precision image-guided tumor resections and photothermal ablation of cancer.